Keterampilan Menulis Mahasiswa PAI pada Artikel Jurnal Internasional dengan BICC - Ahmad Taufiq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Writing international journal articles is an important skill for postgraduate students to contribute to the development of science. This study aims to evaluate the effectiveness of the Blended Intensive Coaching Clinic (BICC) method in improving international journal article writing skills among IAIN Pekalongan postgraduate students. This research method involves the use of a blended learning approach which combines online and face-to-face learning. A number of IAIN Pekalongan postgraduate students are guided intensively through writing clinics, which include online training, face-to-face sessions and structured feedback. Evaluation is carried out through qualitative and quantitative analysis of progress in international journal article writing skills. The research results show a significant increase in international journal article writing skills after participating in the BICC program. Students showed improvements in understanding article structure, writing quality, and ability to construct arguments and research ideas. Direct feedback from supervisors also contributes positively to student development. This research contributes to the understanding of the use of blended learning methods in the context of improving academic writing skills, especially in the context of postgraduate students. The practical implication of this research is that BICC can be an effective approach to improve the quality of graduate students' scientific writing, preparing them for active participation in the international scientific community